Comparison of bridge mamagememt strategies using life-cycle cost analysis - Onoufriou, Toula; Rafiq, Meena Imran; Chryssanthopoulos, Marios K. (My University, 2005)
A comparison of safety characteristics and life-cycle costs for different bridge management strategies is presented in this paper. These strategies are based on regular inspections; on predictive models updated through regular inspections; and on predictive models updated through the use of permanent health monitoring systems. The results for these management strategies for various inspections and health monitoring outputs are presented and discussed. It is concluded that the life cycle costs of concrete structures are strongly influenced by the timings of repairs, and can be reduced considerably by delaying the repairs due to an increase in confidence of predicted performance through inspections and health monitoring data. Furthermore, it is shown that the decisions supported by permanent monitoring systems can result in significant savings whilst maintaining a target safety level of the structures.
Keywords: Health monitoring series; Concrete bridges